ANALISIS STRATEGI MARKETING PT. HNI-HPAI TERHADAP TINGKAT INCOME AGENCY PRODUK SYARIAH DI PT. HERBA PENAWAR ALWAHIDAH INDONESIA - Yusniar Yusniar; Rahmat Mansur (Jurnal Ekonomi Bisnis Syariah, 2020)
Herba Penawar Al Wahidah Indonesia is one of the companies engaged in the medical business. In running his business, he uses a direct selling system in the form of a Multi Level Marketing format. Multi Level Marketing is tiered marketing through a distribution network built by promising consumers (customers) as well as marketing personnel. The agency of this company has been active in recent years and provides increased income to all sales agents. He is interested in seeing and researching the marketing strategy management carried out by the company in increasing its income. A qualitative approach with a descriptive form was chosen to describe the general reality of HPAI's business movements and specifically describe marketing patterns in increasing the company's revenue figures. Data collection is carried out in three forms, namely; observations, interviews, and documentation. The HNI-HPAI marketing system is different from other Multi Level Marketing marketing systems. In HNI-HPAI, a consumer or agency is not required to make product purchases to the upline. There are 4 strategies that are carried out first, there is a pull strategy (pull), the second is strength as a bearer of the push strategy (pusher), the third is the pass strategy (pass), and the fourth is Home Sharing that public relations influence public opinion